Technology Enhanced Learning in Undergraduate Pharmacology through Online Quizzes: A Pedagogical Approach and Medical Students’ Perspective - Sarker, Sujit Kumar; Bhas, Geethanjali; Marakala, Vijaya; Yusuf, Mohammad Abdullah (Journal of Current and Advance Medical Research, 2019)
Background: Technology enhanced learning in medical curriculum is expanding rapidly because of research showing the benefits for learners in terms of engagement, convenience, attainment and enjoyment. Objectives: The purpose of the present study was to explore medical students’ perspective on technology enhanced learning in undergraduate pharmacology. Methodology: This descriptive cross-sectional study was conducted in the Faculty of Medicine during 2016 for a period of three (3) months. Second year MBBS students who were studying in the International Medical School, Management & Science University,Selangor, Malaysia with the age group of equal or more than 18 years of age with both sexes were selected as study population. Several online quizzes were conducted by Quizizz. Data were analysed after online quizzes using semi-structured questionnaire. Results: A total number of 42 students were involved in this study. Among these 35(83.33%) surveyed students were strongly agreed with timing for answering the questions however, 39(92.86%) strongly agreed that quizzes stimulate interest in pharmacology and 28(66.67%) strongly agreed that quizzes improve knowledge and skill in pharmacology. Most of the students suggested to continue online quizzes. Conclusion:Systematic analysis and stratification of students’ perceptions regarding technology enhanced learning initiatives such as online quizzes are essential in gaining insight for educational planning and interventions in pharmacology. Journal of Current and Advance Medical Research 2019;6(1):14-17